Italian conversation - Danesi, Marcel 1946- (Practice makes perfect., 2018)
Learn how to speak Italian fluently and spontaneously. This book gives you helpful instruction on correct pronunciation, grammar, syntax, and word usage, keeping in mind the typical problems of native English speakers like you.